Management of problematic weeds in sugarcane - Singh, V. P.; Kumar, Dileep; Singh, K. K. (Indian Farming, 2018)
Weeds are one of the major challenges in increasing theproductivity of sugarcane. They cause 38 to 76% yield loss depending on the nature of weed flora and duration of crop-weed competition. The total cane yield loss in the country per annum due to weeds is around 25 million tonne (equivalent to 2.5 million tonne of sugar) valued around Rupees 1,500 crore. Sorghum halepense, Cyperus rotundus, Cunodon dactylon, Ipomoea spp., and Striga spp. are the major weeds in sugarcane. Integrated weed management involving pre-emergence application of atrazine@2.0 kg/ha fb trash mulching fb post-emergence application of 2,4-D at 75 day after planting added with one hoeing at 90 day after planting provided seasonlong weed control and the highest productivity of sugarcane and monetary returns.